ChemInform Abstract: The Effect of Indium(III) Triflate in Oxone‐Mediated Oxidative Methyl Esterification of Aldehydes. Issue 7 (18th February 2014) - Mineno, Tomoko; Sakai, Mai; Ubukata, Akira; Nakahara, Kazuhide; Yoshimitsu, Hitoshi; Kansui, Hisao
Abstract Efficient, direct oxidative methyl esterification of aryl aldehydes is achieved using a couple of oxidant (oxone) and In(O‐Tf)3 as Lewis acid.